Application of Adipose-Tissue Derived Products for Burn Wound Healing - Hamid Malekzadeh; Zayaan Tirmizi; José A. Arellano; Francesco M. Egro; Asim Ejaz (MDPI AG, 2023)
Burn injuries are a significant global health concern, leading to high morbidity and mortality. Deep burn injuries often result in delayed healing and scar formation, necessitating effective treatment options. Regenerative medicine, particularly cell therapy using adipose-derived stem cells (ASCs), has emerged as a promising approach to improving burn wound healing and reducing scarring. Both in vitro and preclinical studies have demonstrated the efficacy of ASCs and the stromal vascular fraction (SVF) in addressing burn wounds. The application of ASCs for burn healing has been studied in various forms, including autologous or allogeneic cells delivered in suspension or within scaffolds in animal burn models. Additionally, ASC-derived non-cellular components, such as conditioned media or exosomes have shown promise. Injection of ASCs and SVF at burn sites have been demonstrated to enhance wound healing by reducing inflammation and promoting angiogenesis, epithelialization, and granulation tissue formation through their paracrine secretome. This review discusses the applications of adipose tissue derivatives in burn injury treatment, encompassing ASC transplantation, as well as the utilization of non-cellular components utilization for therapeutic benefits. The application of ASCs in burn healing in the future will require addressing donor variability, safety, and efficacy for successful clinical application.